High‐dose bee venom exposure induces similar tolerogenic B‐cell responses in allergic patients and healthy beekeepers. Issue 3 (20th July 2016) - Boonpiyathad, T.; Meyer, N.; Moniuszko, M.; Sokolowska, M.; Eljaszewicz, A.; Wirz, O. F.; Tomasiak‐Lozowska, M. M.; Bodzenta‐Lukaszyk, A.; Ruxrungtham, K.; van de Veen, W.
Abstract: Background: The involvement of B cells in allergen tolerance induction remains largely unexplored. This study investigates the role of B cells in this process, by comparing B‐cell responses in allergic patients before and during allergen immunotherapy (AIT) and naturally exposed healthy beekeepers before and during the beekeeping season. Methods: Circulating B cells were characterized by flow cytometry. Phospholipase A2 (PLA)‐specific B cells were identified using dual‐color staining with fluorescently labeled PLA. Expression of regulatory B‐cell‐associated surface markers, interleukin‐10, chemokine receptors, and immunoglobulin heavy‐chain isotypes, was measured. Specific and total IgG1, IgG4, IgA, and IgE from plasma as well as culture supernatants of PLA‐specific cells were measured by ELISA. Results: Strikingly, similar responses were observed in allergic patients and beekeepers after venom exposure. Both groups showed increased frequencies of plasmablasts, PLA‐specific memory B cells, and IL‐10‐secreting CD73 − CD25 + CD71 + BR 1 cells. Phospholipase A2‐specific IgG4‐switched memory B cells expanded after bee venom exposure. Interestingly, PLA‐specific B cells showed increased CCR5 expression after high‐dose allergen exposure while CXCR4, CXCR5, CCR6, and CCR7 expression remained unaffected. Conclusions: This study provides the first detailed characterization of allergen‐specific B cells before and after bee venom tolerance induction. The observed B‐cell responses in both venom immunotherapy‐treated patients and naturally exposed beekeepers suggest a similar functional immunoregulatory role for B cells in allergen tolerance in both groups. These findings can be investigated in other AIT models to determine their potential as biomarkers of early and successful AIT responses.